2017
DOI: 10.1016/j.jembe.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of extreme temperature and low salinity on foundational macroalga Fucus vesiculosus in the northern Baltic Sea

Abstract: Climate change has been identified as one of the biggest current drivers of environmental change. Climate model projections for the Baltic Sea forecast increased frequency and duration of extreme temperatures, together with declines in salinity, which are expected to have impacts on the biota. In this experimental study, the interacting effects of low salinity and short-term (8 days) extreme seawater temperatures, followed by an 11-day recovery period, on the foundational macroalga, Fucus vesiculosus, were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 64 publications
(100 reference statements)
1
23
0
Order By: Relevance
“…Climate change is expected to modify all these factors, with the extent of the perturbation varying from one region to another. In general, our current knowledge of the tolerance of marine macroalgae to future climate-change conditions is limited to a few factors, mainly temperature and acidification [7,8], but also salinity [9][10][11]. In the Baltic Sea, a major change induced by climate change will be desalination [12], which will shift the surface water salinity gradient southward and challenge the persistence of marine macroalgae at the low-salinity end of the gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is expected to modify all these factors, with the extent of the perturbation varying from one region to another. In general, our current knowledge of the tolerance of marine macroalgae to future climate-change conditions is limited to a few factors, mainly temperature and acidification [7,8], but also salinity [9][10][11]. In the Baltic Sea, a major change induced by climate change will be desalination [12], which will shift the surface water salinity gradient southward and challenge the persistence of marine macroalgae at the low-salinity end of the gradient.…”
Section: Introductionmentioning
confidence: 99%
“…the modeled trends) illustrates that conclusions on carbon balance differ when considering single species in isolation versus a system perspective. F. vesiculosus is able to withstand a wide range of environmental changes, since the species is exposed to different temperatures along the seasons (Takolander et al 2017). Graiff et al (2015) demonstrated that the temperature for maximum photosynthesis capacity (expressed as maximum relative electron transport rate) was 24 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Graiff et al (2015) demonstrated that the temperature for maximum photosynthesis capacity (expressed as maximum relative electron transport rate) was 24 °C. Takolander et al (2017) found that temperatures beyond 26 °C jeopardize the photosynthetic activity of the macroalgae. In our study, the rates of NPP did not decrease along the temperature gradient and respiration of the Fucus-epiphytes assemblage increased linearly with temperature ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Bays also have shallow anoxic layers due to densely packed organic matter (Revsbech et al 1980). Temperature and salinity have been shown to have synergistic impacts on oxidative stress, such that species may tolerate high temperatures or low salinity, but not in conjunction (Takolander et al 2017). This may explain why the two GoM shifts to brackish environments are accompanied by body size and genome size reductions, but not the Atlantic shift (i.e., L.…”
Section: The Drivers Of Genome Size Evolution In Haustoriidaementioning
confidence: 99%